2020
DOI: 10.3390/atmos11030248
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Characteristics in the Mantaro Basin over Tropical Andes from a Vertically Pointed Profile Rain Radar and In-Situ Field Campaign

Abstract: Information on the vertical structure of rain, especially near the surface is important for accurate quantitative precipitation estimation from weather and space-borne radars. In the present study, the rainfall characteristics, from a vertically pointed profile Radar in the Mantaro basin (Huancayo, Peru) are observed. In summary, diurnal variation of near-surface rainfall and bright band height, average vertical profiles of the drop size distribution (DSD), rain rate, radar reflectivity (Ze) and liquid water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 74 publications
2
28
0
Order By: Relevance
“…highest beam elevation of 3800 m at the full range (100 km) is almost always be typical altitude of the melting layer as reported by [12] for the Andes.…”
Section: Radar Data Preprocessingsupporting
confidence: 71%
See 2 more Smart Citations
“…highest beam elevation of 3800 m at the full range (100 km) is almost always be typical altitude of the melting layer as reported by [12] for the Andes.…”
Section: Radar Data Preprocessingsupporting
confidence: 71%
“…Bright-band effects are rarely seen in the radar data because of the low elevation of the radar site and the sharp pencil beam (2 • vertical) with a center elevation of 0 • . The highest beam elevation of 3800 m at the full range (100 km) is almost always below the typical altitude of the melting layer as reported by [12] for the Andes.…”
Section: Radar Data Preprocessingmentioning
confidence: 48%
See 1 more Smart Citation
“…The central Andes witness convective (30%) and stratiform (70%) precipitation, contributing with 63.3 and 36.7% of total rain, whereas in the Amazon-Andes transition those percentages and the contribution to cumulative rain attain similar values (31 and 69%, respectively). Over the central Peruvian Andes, and using a vertically pointed profile rain radar installed in the Mantaro Basin, Kumar et al (2020) show that most of the bright band height (an indication for the melting zone) over this region vary between 4.3 and 4.7 km. An example of the vertical profile of radar reflectivity is shown in Figures 6E,F.…”
Section: Southern Tropical Andesmentioning
confidence: 98%
“…Compared with conventional scanning weather radars, vertically pointing short-wave radars have advantages in the observation of stratiform precipitation vertical structures because of their higher spatiotemporal resolution and sensitivity. For instance, Kumar et al [12] used gradients in profiles of radar reflectivity and Doppler velocity from a Kaband Doppler radar to identify the BB, noting that radar reflectivity significantly increases with decreasing height above the BB, whereas vertical variations of it below the BB depend on rain rate. Jha et al [13] and Devisetty et al [14] suggested that an appropriate threshold value of −22 dB for the radar linear depolarization ratio, measured using a Ka-band zenith radar, can be associated with the top and bottom heights of the BB.…”
Section: Introductionmentioning
confidence: 99%